An overview of proteomic methods for the study of 'cytokine storms'. (1st February 2021) - David, Paul; Hansen, Frederik J.; Bhat, Adil; Weber, Georg F.
ABSTRACT: Introduction : The cytokine storm is a form of excessive systemic inflammatory reaction triggered by a myriad of factors that may lead to multi-organ failure, and finally to death. The cytokine storm can occur in a number of infectious and noninfectious diseases including COVID-19, sepsis, ebola, avian influenza, and graft versus host disease, or during the severe inflammatory response syndrome. Area covered : This review mainly focuses on the most common and well-known methods of protein studies (PAGE, SDS-PAGE, and high- performance liquid chromatography). It also discusses other modern technologies in proteomics like mass spectrometry, soft ionization techniques, cytometric bead assays, and the next generation of microarrays that have been used to get an in-depth understanding of the pathomechanisms involved during the cytokine storm. Expert opinion : Overactivation of leukocytes drives the production and secretion of inflammatory cytokines fueling the cytokine storm. These events lead to a systemic hyper-inflammation, circulatory collapse and shock, and finally to multiorgan failure. Therefore, monitoring the patient's systemic cytokine levels with proteomic technologies that are redundant, economical, and require minimal sample volume for real-time assessment might help in a better clinical evaluation and management of critically ill patients.